The effect of foliar fertilizer and pesticide methomyl in tea plantation after infested by pest: (2) The effect on population and attack intensity of Empoasca flavescens - Fauziah, Fani; Haq, Muthia Syafika; Karyudi, Dr.; Rosyadi, Achmad Imron (Research Institute for Tea and Cinchona, 2015)
The aim of this research was to obtain the effect of insecticide combination with nitrogen and zinc foliar fertilizers to Empoasca flave-scens. An experiment was conducted at Gam-bung Experimental Garden, Bandung, West Java. The trial was arranged in a randomized complete block design with nine treatments (A)methomyl; (B) methomyl + ZnSO4 1%; (C) me-thomyl + ZnSO4 2%; (D) methomyl + N 1%; (E) methomyl + N 1% + ZnSO4 1%; (F) metho-myl + N 1% + ZnSO4 2%; (G) methomyl + N 2%; (H) methomyl + N 2% + ZnSO4 1%; and (I) methomyl + N 2% + ZnSO4 2%, replicated three times. Each unit consisted of experiments is 40 plants. The treatments comprised: concen-tration of methomyl 0,5 gram/l with sprayed volume 200 l/ha. The level concentrations of nitrogen and zinc were 1% and 2%. The appli-cation of treatments was sprayed six times after plucking with 12 days interval, respectively. The population and intensity of E. flavescens attack were measured at the time of plucking. The effectiveness of treatment on the population as well as attack intensity of Empoasca con-ducted by measuring the rate of decline through a linear regression approach. The results showed that all of the treatments could reduce the population as well as the attack intensity of E. flavescens but there were no significantly different among others and were comparable to the chemical insecticide treatment. The fastest rate of decline were indicated by the treatment methomyl + N 2% + ZnSO4 1% and methomyl + N 2% + ZnSO4 2%.